Project Based Learning Berbantuan Canva sebagai Alternatif Pembelajaran Bahasa Indonesia pada Era VUCA - Nabila, Syalha Azzahra; Heryadi, Dedi; Lisnawati, Iis (Proceedings Series on Social Sciences & Humanities, 2024)
This study aims to determine the effect of the Project Based Learning learning model assisted by Canva media to write biographical texts. The research method used is a quasi-experimental method. Data collection techniques used are observation, interviews, and tests. The population of the study was grade X SMK students. The research sample was class TKJ 1 (experimental class) and class TKJ 2 (control class). The results of the study showed that the average value of the ability to write biographical texts in the experimental class is higher than the average value in the control class (76.27> 69.13). The results of the Wilcoxon test show that the Asymp. Sig value is 0.000 <0.05. This shows that the Project Based Learning learning model assisted by Canva media has a significant effect on the ability to write biographical texts of class X students of SMK Al Ilyas Malangbong in the 2023/2024 academic year.